Varistor property of SnO2 center dot CoO center dot Ta2O5 ceramic modified by barium and strontium - Dhage, S. R.; Ravi, V.; Yang, O. B. (Journal of Alloys and Compounds, 2008)
The influence of an alkali earth (Ba/Sr) element in small quantities (< 1 at.%) on non-linear electrical properties of 98.5% SnO2 + 1% CoO + 0.5% Ta2O5 (all in at.%) varistor system has been investigated. The non-linear coefficient increases from 33 to 52 whereas breakdown field strength varies 5025-6050 V cm(-1) for the barium-doped samples. In case of strontium-doped specimens moderate increase in non-linear coefficient but significant increase in breakdown field is observed. It is proposed that due to ionic size misfit, Ba and Sr segregates to grain boundaries thereby modifying their barrier properties. The contribution from grain boundary phase to the electrical property is confirmed by the impedance analysis. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Oxide materials; scanning electron microscopy; Sintering